Heart Rate Regulation Using Cardiac Pacemaker System with Adaptive Neuro-Fuzzy Inference System Based Fractional-Order PID Controller - Nigatu, Abeme (ASTU, 2022)
Nowadays, heart disease is becoming the main cause of death worldwide. Therefore, the need arises to find advanced approaches to keep the patients safe. An implantable cardiac pacemaker is a standardized medical electronic device for the management and treatment of cardiac arrhythmias aimed at improving healthcare. This paper describes the nonlinear control of the heart rate model. ECG signals were generated using Zeeman's heart rate model. The existing heartbeat model was analyzed, and revised by consolidating the con trol inputs and adding a control mechanism as a pacemaker. In this study, the FOPID con troller and ANFIS-based FOPID controller were applied to the heartbeat model to track and generate real ECG signals. The proposed method ANFIS-based FOPID controller has shown better performance in terms of tracking ECG signal of the actual data, obtained from the MIT- Boston’s Beth Israel Hospital (BIH) and the physioNet database by eliminating chattering compared with the use of FOPID controller that increases the life span of a pace maker. In addition, since the heartbeat pacemaker is disturbed by the brain signal, the ro bustness of the system to disturbance was analyzed. On the other hand, in this thesis, an ANFIS-based FOPID controller was developed to improve the performance of cardiac pacemakers that regulate heart rate. The design of the ANFIS-based FOPID controller en sures the stability and performance of the rate-adaptive pacing system, achieves bet ter heart rate tracking and regulation at desired values. The developed control sys tem was successfully validated using three cases of preset heart rates. The proposed model is designed, tested, and simulated along with tuning the controller gains using Matlab/Sim ulink software. The proposed controller performance for tracking and regulating different heart rates has been compared with FOPID and GA-tuned FOPID controllers. The com parison results show that the proposed system improved the parameters of cardiovascular system response in terms of stability, steady-state error and transients response.
Keywords: ANFIS, ECG signals, FOPID, GA, heartbeat model, heart rate, pacemaker